Mudança estratégica, dinâmica das rotinas e recursos-em-uso: uma análise processual em uma instituição de ensino superior no contexto do ensino a distância - Rosa, Rodrigo Assunção (2020)
In this PhD dissertation, I analyze how actors transform resources within and between organizational routines in response to resource constraints of a new commercial strategy. To this end, I seek to contribute to some of the gaps in the recent literature on organizational strategy and routines, considering that the internal analysis of routines has still been treated as a black box in research on strategic change. To achieve these goals, I conducted an in-depth single case study at the distance education unit (DEU) of a private university (UAlpha). UAlpha crossed by rapid changes in the legislation and market environment, and internal changes in its DEU, which allowed to characterize the relevance and contribution of the case to the purposes of understanding the phenomena. During the data collection period, I followed the DEU's internal change process as a non-participating observer for five months, triangulating the observations collected with semi-structured interviews and with secondary sources and internal documents. The use of different qualitative analysis techniques with the support of Atlas.ti software allowed me to elaborate a processual theoretical-empirical model that demonstrate the relationship between the contextual and internal changes of the organization, with a central interest in the internal dynamics within and between organizational routines. The focus of the narratives is on how a new commercial strategy impacted the chain of activities and resources of a focal routine (teaching routine), resulting in a new internal scenario characterized by the restriction of time, space and identity in the focal routine. Therefore, I present how the actors in the teaching routine and some interdependent routines mobilized resources to respond to the new condition imposed by the strategy. The analysis allowed me to identify three core resourcing processes (emergent, configurational and identity) from which actors seek to respond emergently to the new strategic condition of the organization within and between routines. In addition to the intended theoretical contributions, the findings also allowed me to offer practical implications for strategists, managers and employees, and suggestions for future advances in these relevant fields of research.